Relationship between emotional quotient and the level of job satisfaction among secondary school teachers - Jusoh, Rosnani; Mhamat Nasudin, Noorhidayati Nasriah (2012)
Emotional quotient (EQ) identified as an important predictor for workplace success. It reflects the ability to deal successfully with other people and with feelings, including professional and personal pursuits. Quality emotions and feelings help teachers give their best job performance and the higher teachers’ EQ, the more likely they are to be successful in their profession. This study is to examine the relationship between emotional quotient and the level of job satisfaction among secondary school teachers. For this purpose 140 teachers involved in this study. Questionnaire was used to gather all data related to the study. The result of the study showed that there was a significant relationship between the level of EQ and the level of job satisfaction.